Detection of water quality parameters in Hangzhou Bay using a portable laser fluorometer. Issue 1 (15th April 2015) - Chen, Peng; Pan, Delu; Mao, Zhihua; Tao, Bangyi
Highlights: A laser fluorometer for detecting water quality parameters was developed. The detection limit was 0.2 μg/L, 0.75 μg/L and 1 mg/L for chl-a, CDOM and TSM. The baseline drift was only 0.45% per hour. Laser fluorescence distribution and characteristic in Hangzhou Bay were analyzed. Abstract: A field, light-weight laser fluorometer based on the method of laser induced fluorescence was developed for water quality monitoring. The basic instrument configuration uses a high pulse repetition frequency microchip laser, a confocal reflective fluorescent probe and a broadband hyperspectral micro spectrometer; it weights only about 1.7 kg. Simultaneous estimates of three important water quality parameters, namely, chlorophyll a (chl-a), colored dissolved organic matter (CDOM), and total suspended matter (TSM) measured by the laser fluorometer were observed to agree well with those measured by traditional methods (0.27–0.84 μg L −3 chl-a, R 2 = 0.88; 0.104–0.295 m − 1 CDOM absorption, R 2 = 0.90; and 59.8–994.9 mg L − 3 TSM, R 2 = 0.86) in Hangzhou Bay water. Subsequently, distribution and characteristics of CDOM and chl-a laser fluorescence in Hangzhou Bay were analyzed, which will enhance our understanding of biogeochemical processes in this complex estuarine system at high-resolution, high-frequency and long-term scale.